Game audio programming : principles and practices - Somberg, Guy, ....- (Boca Raton : CRC Press, Taylor & Francis Group, 2017)
Welcome to Game Audio Programming: Principles and Practices! This book is the first of its kind: an entire book dedicated to the art of game audio programming. With over fifteen chapters written by some of the top game audio programmers and sound designers in the industry, this book contains more knowledge and wisdom about game audio programming than any other volume in history. One of the goals of this book is to raise the general level of game audio programming expertise, so it is written in a manner that is accessible to beginners, while still providing valuable content for more advanced game audio programmers. Each chapter contains techniques that the authors have used in shipping games, with plenty of code examples and diagrams. There are chapters on the fundamentals of audio representation and perception; advanced usage of several different audio middleware platforms (Audiokinetic Wwise, CRI ADX2, and FMOD Studio); advanced topics including Open Sound Control, Vector-Based Amplitude Panning, and Dynamic Game Data; and more! Whether you're an audio programmer looking for new techniques, an up-and-coming game developer looking for an area to focus on, or just the one who got saddled with the audio code, this book has something for you. Cutting-edge advanced game audio programming concepts, with examples from real games and audio engines Includes perspectives of both audio programmers and sound designers on working and communicating together Coverage not just on game audio engine design, but also on implementing audio tools and working with sound designers providing a comprehensive perspective on being an audio programmer.
Includes index.
Keywords: Computer game music; Computer games -- Programming; Computer sound processing; Sound -- Recording and reproducing -- Digital techniques